Estudio de calidad de energía eléctrica en la instalación de Laboratorios Stein, Costa Rica - Brenes-Hernández, Luis Alejandro (Instituto Tecnológico de Costa Rica, 2018)
Due to previous indications of events related to the power quality supplied by the distribution company to Laboratorios Stein, it is decided to make a representative power quality study of the whole existing electrical installation. The project seeks to present the limits and criteria of the different standards established to regulate this subject, such as the national standard AR NT SUCAL 2015 and the international ones such as the IEEE standards, to characterize the current state of the power quality, with which the plant works, pointing out those events that are outside the ranges, and proposing their respective mitigation. In addition, the written document serves as the basis for the power quality studies of Energética Soluciones y Consultoría IAC
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2018.
Keywords: Calidad; Energía; Armónicos; Mitigación; Tensión; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electrical engineering